Secretory Leukocyte Protease Inhibitor: Immunohistochemical Evidence Supporting a Fallopian Tube Origin for Serous Papillary Carcinoma - Sun, MD, PhD, Jianlan (North American Journal of Medicine and Science, 2009)
Serous papillary carcinoma (SPC) represents the most common histological type of ovarian carcinoma, which is the fifth leading cause of cancer-related death in women in the United States.1 The tissue of origin for SPC remains controversial. It is believed by many authors that the cancer arises from the surface epithelia of the ovary or the cells that line ovarian inclusion cysts.2-3 In this theory, the ovarian surface epithelium (OSE), usually flattened with no distinct features, undergoes Mullerian metaplasia and through possible undefined molecular events, acquires serous papillary morphology during malignant transformation. A contrasting opinion is that SPC may arise from the fallopian tube (FT), this supposition based on the morphologic resemblance of SPC to the fimbriated end of the FT. A recent report4 investigating the patterns of gene expression among different histotypes of epithelial ovarian cancer showed strong correlation of expression profile of serous papillary carcinoma with that of the fallopian tube. [N A J Med Sci. 2009;2(2):42-43.]